Adaptive Governance dalam Pengelolaan Badan Usaha Milik Desa di Desa Sekapuk Kabupaten Gresik - Nanda Syarifudin Fanani; Ertien Rining Nawangsari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the practice of Adaptive Governance carried out by the Village Government by utilizing the potential of natural resources that have built the democratization of the village economy or turning potential into profit through BUMDes. The approach method used in the research is descriptive qualitative. Data were obtained through observation, interviews, documentation. From the results obtained, it shows that the practice of adaptive governance carried out by BUMDes Desa Sekapuk has been effective in achieving the desired cooperation, because in the output assessment, namely the existence of (1) in the system, BUMDes Desa Sekapuk can be said to be part of a polycentric and multi-layered institution because in a polycentric system there is a multi-stakeholder governance pattern. (2) participation and collaboration since the BUMDes was reactivated after a long period of non-operation is now quite good and effective in collaboration. (3) independent and networked organization, the governance of BUMDes Desa Sekapuk can be said to be an arena for all parties to offer ideas, ideas, and innovations. (4) learning and innovation have been very good where Mr. Abdul Halim himself as the Village Head and also the actors of BUMDes Desa Sekapuk learned a lot from an experience at that time.